Chicory supplementation improves growth performance in juvenile ostriches potentially by attenuating enteritis - Li, Meng; Abouelfetouh, Mahmoud M.; Salah, Eman; Kiani, Faisal Ayub; Nan, Sha; Ding, Mingxing; Ding, Yi (Frontiers in Veterinary Science, 2024)
IntroductionEnteritis and dysbiosis are the major causes of high morbidity and mortality of juvenile ostriches. Chicory (CC) has been proven to have excellent antioxidant, anti-inflammatory, and antibacterial activities. However, it’s unclear whether CC could improve the survival rate of juvenile ostriches by relieving enteritis and correcting dysbiosis.Materials and methodsSouth African ostrich hatchlings (Struthio camelus domesticus) were fed with and without a CC-supplemented diet, and the body weight gain and mortality were compared over 4 months of age. Fresh fecal samples of clinically healthy ostriches were collected, and 16S DNAs were analyzed. Moreover, ostrich chicks with LPS-induced enteritis were fed with different dosages (0, 20, 40, and 80 mg/kg) of chicoric acid (CA), a major bioactive component of CC, for five consecutive days. The expression levels of tight junction (TJ)-related proteins and inflammatory mediators in the ilea were detected with western blot and immunofluorescence.ResultsThe ostrich chicks fed on the CC-supplemented diet began to increase in weight at the 1st month of age and became remarkably heavier at the fourth month (p < 0.01) compared with those fed on the non-CC-supplemented diet. Additionally, the mortality percentage was lower in the chicks fed on the CC-supplemented diet than those fed on the non-CC-supplemented diet (19% vs. 36%, respectively). The diet with the CC supplementation significantly increased the abundance of Phascolactobacteria (linear discriminant analysis; LDA >4) and Bacteroidota (26.7% vs. 17.7%, respectively) as well as decreased the enrichment of Clostridium (5.0% vs. 9.1%, respectively) in the ostrich ilea compared to the diet without CC. The supplementation of CA at a dose of 80 mg/kg significantly increased the expression level of ZO-1 and claudin-3 (p < 0.0001) and suppressed the levels of IL-1β, IL-6, and TNF-α (p < 0.0001) in ostriches with LPS-induced ileitis.ConclusionOur results substantiate that CC or CA supplementation in a diet could effectively improve growth performance and reduce mortality in juvenile ostriches via modulating the gut microbiota and attenuating enteritis.